Debt Dilution and Sovereign Default Risk - Martinez, Leonardo (IMF Working Papers; Working Paper ;, 2011)
We propose a modification to a baseline sovereign default framework that allows us to quantify the importance of debt dilution in accounting for the level and volatility of the interest rate spread paid by sovereigns. We measure the effects of debt dilution by comparing the simulations of the baseline model (with debt dilution) with the ones of the modified model without dilution. We calibrate the baseline model to mimic the mean and standard deviation of the spread, as well as the external debt level, the mean debt duration and a measure of default frequency in the data. We find that, even without commitment to future repayment policies and withoutcontingency of sovereign debt, if the sovereign could eliminate debt dilution, the number of default per 100 years decreases from 3.10 to 0.42. The mean spread decreases from 7.38% to 0.57%. The standard deviation of the spread decreases from 2.45 to 0.72. Default risk falls in part because of a reduction of the level of sovereign debt (36% of the face value and of 11% of the market value). But we show that the most important effect of dilution on default risk results from a shift in the set of government's borrowing opportunities. Our analysis is also relevant for the study of other credit markets where the debt dilution problem could be present.